Pemanfaatan Kulit Jeruk Purut Teraktivasi Sebagai Adsorben Alternatif Untuk Penyerapan Ion Logam Zn (II) - Muhammad Furqan Adhi; Rajue Marzyan; Medyan Riza; Farid Mulana (Jurnal Inovasi Ramah Lingkungan, 2021)
Environmental pollution by liquid waste containing Zn heavy metal ions will adversely affect the environment and the health of organism. To reduce the negative impacts required appropriate technology, cheap and effective. In this study used the adsorption method to overcome the negative impact of heavy metal ions Zn. This study aims to make the peel of citrus hystrix D.C as an activated adsorbent to absorb Zn metal ions. Initial treatment of citrus hystrix D.C which has been made into adsorbent is cleansing of dirt and dried in the oven, then soaked with KOH 0.5 M. Then, each citrus hystrix D.C peel is activated by three different activator that is citric acid 1,6 M, acid 1.6 M tartaric acid and 1.6 M. maleic acid. In the adsorption process used variations of Zn concentration of adsorbent metal ions (40, 80, 200, 400 mg / L), optimum contact time (0, 30, 60, 90, 120 , 150, 180 min), 80 rpm stirrer speed, temperature 27ºC and pH 7. The adsorption process procedure that has been carried out, the filtrate of adsorbat will be analyzed using AAS to find out how many Zn metal ions were adsorbed. The result of analysis obtained in this study shows that the most optimum time to conduct Zn metal adsorption process is 120 minutes, with absorption capacity of 33.181 mg / g and efficiency 82.95%. Maleic acid activator 1.6 M is very effective to activate the peel of citrus hystrix D.C.